2018
DOI: 10.1001/jamapsychiatry.2018.2318
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neuroimaging Measures of Emotion Processing and Regulation Neural Circuitries With Symptoms of Bipolar Disorder in Offspring at Risk for Bipolar Disorder

Abstract: Greater anterior cingulate cortex activity and functional connectivity during emotion regulation tasks may be specific markers of BD risk. These findings highlight potential neural targets to aid earlier identification of and guide new treatment developments for BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Previous neuroimaging studies have reported deviation of brain structure among BD patients, including thinner cortex, increased volume, and surface of the right inferior frontal gyrus (Hanford et al, 2016, Roberts et al, 2017, Drobinin et al, 2019. One longitudinal neuroimaging study found greater anterior cingulate cortex activity and connection with amygdala while processing emotional regulation tasks in offspring of parents with BD; this study provides some evidence for the association of BD in families with de cits of neurodevelopment (Acuff et al, 2018).…”
Section: Offspring With Bdsupporting
confidence: 51%
“…Previous neuroimaging studies have reported deviation of brain structure among BD patients, including thinner cortex, increased volume, and surface of the right inferior frontal gyrus (Hanford et al, 2016, Roberts et al, 2017, Drobinin et al, 2019. One longitudinal neuroimaging study found greater anterior cingulate cortex activity and connection with amygdala while processing emotional regulation tasks in offspring of parents with BD; this study provides some evidence for the association of BD in families with de cits of neurodevelopment (Acuff et al, 2018).…”
Section: Offspring With Bdsupporting
confidence: 51%
“…49 However, a preponderance of studies of individuals with BD have reported deficits in emotion regulation, excessive self-referential thinking, and rumination in depressed states, and reduced volumes and connectivities in prefrontal and limbic networks. These deficits have also been consistently implicated as risk factors for predicting the onset of BD in structural MRI, 12 task-based fMRI, [50][51][52] and resting state fMRI 53 studies of high-risk youths. It may be that the high-risk youth in our study were more depressed, treatment seeking, and at a different stage of illness than those in prior studies, showing increases in VLPFC-aDMN connectivity rather than the expected decreases in prefrontal and limbic connectivity that have been observed in youths with and at risk for BD.…”
Section: Discussionmentioning
confidence: 96%
“…Considering that limbic and associated brain structures, such as the amygdala, anterior cingulate cortex, hippocampi, prefrontal cortex, and basal ganglia (structures that play essential roles in cognitive processes like memory, attention, emotion, and perception) contain many enzymes and cytokines involved in an inflammatory response ( Raz & Rodrigue, 2006 ; Sudheimer et al, 2014 ; Rosenblat et al, 2015 ; Wang et al, 2015 ; Bortolato et al, 2015 ; Elias et al, 2017 ; Acuff et al, 2018 ); therefore, according to the available evidence, there is a probability of occurrence of these cognitive defects in these patients, which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%